EFFORTS OF THE POLICE TRAFFIC CORPS TO OVERCOME THE PROBLEM OF ILLEGAL VEHICLE LICENSE PLATES - Joshua Leonard Aldriano Marbun; Surya Nita; Sutrisno Sutrisno (Transpublika Publisher, 2024)
This research aims to analyze the efforts made by the Police Traffic Corps in tackling the use of illegal vehicle number plates and identify the obstacles faced in its law enforcement. This research uses a qualitative method with a descriptive-analytical approach, involving in-depth interviews with Korlantas (Traffic Corps) officers, legal experts, and direct observation. The results show that Korlantas Polri has implemented several strategies, such as the implementation of Electronic Registration and Identification (ERI) and electronic ticketing (e-Tilang), as well as special operations to detect and crack down on fake license plates. Nonetheless, this study found significant obstacles, including technological limitations, uneven infrastructure, and low public legal awareness. The implications of this research underscore the need for strengthening cross-agency cooperation, developing more sophisticated detection technologies, and public education campaigns to improve the effectiveness of law enforcement against illegal license plates.